PENINGKATAN PERKEMBANGAN KOGNITIF MELALUI PERMAINAN BALOK GEOMETRI PADA ANAK USIA 3-4 TAHUN DI PPT MAWAR 01 AR-RACHMAN SURABAYA - Masruroh . (Universitas Narotama, 2019)
One of the obstacles that researchers encountered in PPT Mawar 01 is the lack of understanding of the child's cognitive to recognize geometric shapes and distinguish similar size. Researcher overcome this problem through the geometry beam game as it can be one attractive alternative as a learning medium. Result of the research using ClassAction Research indicates a gradual improvement in children's ability to recognize geometric shapes. Increased ability to know the geometric shapes seen on the indicator of the ability to know, understand, and apply the geometric shapes in play. Before the given action, the value of the average grade of 33%. After giving the action through learning by applying beam game in Cycle I value the class average increased to 60% and in Cycle II class average value increased by 87% to reach the 75% indicator of success. Its showed that learning with games beam geometry of color can enhance early childhood cognitive development on material familiar geometric shapes. Keywords: geometry beam, medium of learning, cognitive development